Evaluation of photoresponse in solution-processable ZnO thin film transistor for radiative sensor applications - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2012)
Thin film transistor based on the spin-cast ZnO channel layer was fabricated with SiO2 dielectric layer on Si substrate. The ZnO active layer grown by sol-gel spin-cast caused an increase in the field-effect mobility compared to those of the ZnO TFTs with the channel layer grown by zinc acetate precursor. Under light illumination, the ZnO-TFT in turn-off state exhibited a high drain current, which is 12.82 times higher than dark drain current, whereas in turn-on state is 9.43 times. The photosensing behavior of thin film transistor based on the spin-cast ZnO channel layer indicated more pronounced under a depletion region of 0V gate bias. The obtained results indicate that the ZnO layer spin coated on SiO2 gate layer can be an effective and promising way to increase factor for improving the device performance and for light detecting of ZnO thin film transistor and the studied thin film phototransistor can be used in optoelectronic applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Thin film transistor; Light photosensing; Field effect mobility